A Diet Enriched with Red Sorghum Flaked Biscuits, Compared to a Diet Containing White Wheat Flaked Biscuits, Does Not Enhance the Effectiveness of an Energy-Restricted Meal Plan in Overweight and Mildly Obese Adults. (3rd April 2017) - Stefoska-Needham, Anita; Beck, Eleanor J.; Johnson, Stuart K.; Batterham, Marijka J.; Grant, Ross; Ashton, John; Tapsell, Linda C.
Abstract: Objectives : Whole grain sorghum is a promising ingredient in foods, especially those targeting satiety and weight control. This study aimed to test weight loss effects of a whole grain red sorghum product incorporated into an energy-restricted diet. Methods : Sixty subjects (46 females) were randomized to either a sorghum (intervention) or white wheat (control) group, receiving 45 g of flaked cereal biscuits to include daily in their prescribed diets for 12 weeks. Primary outcome was weight loss. Secondary outcomes included plasma glucose, glycosylated hemoglobin (HbA1c), insulin, total cholesterol, high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), triacylglycerides (TAG), interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor alpha (TNF-α), high-sensitivity C-reactive protein (hs-CRP), and total antioxidant capacity (TAC; measured at 0 and 12 weeks). Results : After 12 weeks, there were no significant differences in weight loss or any clinical variables between a wheat control and sorghum cereal group in an energy-restricted diet. Equivalent amounts of weight were lost ( p = 0.369) in both groups, and the majority of clinical indices such as fasting glucose, insulin, cholesterol, and key inflammatory biomarkers showed significant beneficial changes over time ( p < 0.05). Conclusions : Although both groups experienced significant weight loss and general improvement in a number of clinical measures, no effects appeared specifically related to sorghum consumption. Further clinical trials are necessary to establish an evidence base for weight loss effects from chronic sorghum intake. Sorghum represents a viable, gluten-free grain alternative in the formulation of novel food products.